The Effect of Baby Massage on Baby Weight - Sari, Dewi Kartika; Halimatus Saidah; Akhmad; Sri Lestari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
Baby massage is a massage that is done closer to fine strokes or tactile stimulation done on the surface of the skin. Data from a preliminary survey conducted in Tunjung Village, Udanawu District, Kabupaen, Blitar stated that out of 10 infants aged 0-6 months, 6 of them (60%) did not experience weight gain. And 3 of them who did not gain weight said their children had never been in a baby massage. This type of research is a pre-experimental study with a two-group posttest with control design The population to be used in this study is all infants in Tunjung Village with the age of < 1 year in January 2023. The sampling technique uses Simple Random sampling. The samples in this study were 32.16 for the control group and 16 for the treatment group. Treatment by giving baby massage is done 2x a week for 15 minutes within 4 weeks. The statistical test used the Mann Whitney. Based on the statistical test carried out obtained by Asymp. Sig (2-tailed) of 0.007 < (α = 0.05), then Ho was rejected and H1 was accepted meaning that there was a difference in baby weight after baby massage between the control group and the treatment group. It is expected that baby massage can be routinely done so that the baby's weight increases and growth runs normally.